Middle-Class Entrepreneurship and the Effect of Social Capital - Xavier Ordenana; Elizabeth Arteaga (Inter-American Development Bank (IDB), 2012)
This paper surveys Ecuadorian entrepreneurs to ascertain the differences between middle-class and upper-class entrepreneurs and identify the variables associated with the success of a business. The paper also explores the variables that can determine the probability of upward intergenerational mobility. The paper finds that, although the level of social capital among Ecuadorian entrepreneurs is weak, it positively affects the chances of being a dynamic entrepreneur.
Keywords: L26; M13; 330